Phylogenetic Study of Curvularia on Sorghum from Indonesia Based on ITS rDNA Sequence - Iman Hidayat; Indriati Ramadhani (Jurnal Mikologi Indonesia, 2019)
Seven species of Curvularia were recorded from Indonesia, including species that pathogen to sorghum (Sorghum bicolor). The present study aims to determine four isolates of Curvularia isolated from sorghum in Indonesia using a combination of molecular phylogenetic analysis based on internal transcribed spacer (ITS) rDNA sequence and morphological examination. The results showed that the four isolates were genetically closed to C. lunata and C. dactyloctenicola. The morphological examination also insufﬁcient to determine the identity of the four Curvularia isolates from sorghum until species level. Therefore, additional sequences from the partial fragments of the glyceraldehyde-3-phosphate dehydrogenase and the translation elongation factor 1-a genes are necessary to determine the identity of the Curvularia sequences isolated from sorghum in Indonesia until species level.